Dampak Jangka Waktu Jatuh Tempo, Tingkat Suku Bunga Dan Nilai Kurs Terhadap Harga Obligasi Pemerintah - Manurung, Nursania; Juwita, Ratna (MDP Student Conference, 2024)
The study examines the effects of maturity, interest rates, and exchange rates on government bond prices. The population of this study included 78 government bonds using purposive sampling method. The results of this study show that maturity and exchange rates do not have a significant impact on bond prices. Interest rates have a negative impact on bond prices.